2005
DOI: 10.1007/bf03194490
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of wolf predation on red deer in the Bieszczady Mountains, Poland

Abstract: OEmietana W. 2005. Selectivity of wolf predation on red deer in the Bieszczady Mountains, Poland. Acta Theriologica 50: 277-288.A pattern of wolf Canis lupus Linnaeus, 1758 predation on red deer Cervus elaphus Linnaeus, 1758 was studied in Bieszczady Mountains in 1991-2002. In total 324 remains of red deer > 4 months old, killed by wolves throughout the year, were found. The sex, age and bone marrow fat content of wolf kills were compared with the same characteristics within the free living red deer population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…<1 year) in many study areas (see Okarma 1995 for a review;Gula 2004;Jędrzejewski et al 2000) and in particular individuals between 10 and 35 kg (Meriggi et al 1996;Capitani et al 2004). Likewise, red deer calves were generally selected (Jędrzejewski et al 2000;Gazzola et al 2005;Nowak et al 2005;Smietana 2005). For roe deer, different studies produced different results.…”
Section: Prey Selectionmentioning
confidence: 99%
“…<1 year) in many study areas (see Okarma 1995 for a review;Gula 2004;Jędrzejewski et al 2000) and in particular individuals between 10 and 35 kg (Meriggi et al 1996;Capitani et al 2004). Likewise, red deer calves were generally selected (Jędrzejewski et al 2000;Gazzola et al 2005;Nowak et al 2005;Smietana 2005). For roe deer, different studies produced different results.…”
Section: Prey Selectionmentioning
confidence: 99%
“…The aim of this paper is to analyse first data on red deer spatial behaviour in the Carpathians, because no data are yet available from this area; however, some preliminary results have been presented in the past (Kropil et al 2005(Kropil et al , 2009) and in general, very few related studies have been carried out in this region (Okarma 1984(Okarma , 1991Nowak et al 2005;Smietana 2005). In particular, the aims of this study are as follows: (i) to present first data on home range sizes at two temporal scales (annual and seasonal) of 20 male red deer monitored for several consecutive years in the Western Carpathians using three home range-estimating methods; (ii) to show distinct patterns of spatial behaviour, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the feeding ecology of the wolf Canis lupus have been conducted in North America (Mech 1970, Hoskinson & Mech 1976, Fuller & Keith 1980, Holleman & Stephenson 1981, Ballard et al 1987, Dale et al 1994, Schmidt & Mech 1997). In Europe, there have been various studies on wolf diet, some of which showed wild ungulates as the wolf's main prey (Jedrzejewski et al 1992, Smietana & Klimek 1993, Mattioli et al 1995, Okarma 1995, Meriggi et al 1996, Andersone‐Lilley & Ozolins 2004, Gazzola et al 2005, Smietana 2005, Nowak et al 2005, Valdmann et al 2005). However, the feeding habits of Iberian wolves Canis lupus signatus have received little attention (Guitián et al 1979, Salvador & Abad 1987, Cuesta et al 1991, Urios 1995) and the studies performed have shown that the species' food habits are highly variable depending on the areas in which the species occurs.…”
mentioning
confidence: 99%